Hubungan Pusat Kendali dengan Strategi Koping Orang Tua dari Anak Kanker Yang Menjalani Pengobatan Kemoterapi - Dewi, Nela Yuliya; Lestari, Dhian Ririn; Agustina, Rismia (Universitas Muhammadiyah Magelang, 2021)
Cancer is the main cause of death in children, the majority of treatment is chemotherapy. besides having a therapeutic effect, chemotherapy also has a psychological impact on children and their parents. Among other disorders of sleep, anxiety, stress to depression. Coping strategies can be used to eliminate or reduce stress from stressors. Locus of Control affects personal coping strategies in tolerating the threats that may cause stress or solve the problem. The aim of this research was to find the correlation of locus of control with parents’ coping strategy who have child with cancer undergoing chemotherapy in Hematology Oncology pediatric ward at Ulin Hospital of Banjarmasin. 60,5% of respondents showed the using of Internal Locus of Control. 94,7% of respondents indicated the using of Problem Focused Coping. Fisher Exact analysis showed the p value of 0,509 which indicated that there was no correlation of Locus of Control with Parents’ Coping Strategies who have child with cancer undergoing chemotherapy.